Tourism Information System for the East Kalimantan Provincial Tourism Office - Raodatul Annisa; Eny Maria; Annafi Franz (Politeknik Pertanian Negeri Samarinda, 2025)
Restrictions on activities carried out by the government to suppress the spread of COVID-19, which has lasted for two years, have disrupted community activities. This causes people to carry out activities online or online through digital-based platforms. The use of computer technology for the application of information systems and business is very necessary. This research uses the Waterfall Model System Development Life Cycle (SDLC) development method using data analysis and system design, namely Unified Modeling Language (UML) . This travel information system aims to assist the marketing department in the Tourism Office in conducting tourism promotions and conveying information about travel to consumers or visitors such as tourists. For visitors, this system functions to order travel at the destination by selecting a destination, then the system will take the tour detail page and trip list. Then the trip list section will provide a booking order, after completing the required data input, the system will display a visitor dashboard page to upload proof of payment.